The Influence of Entrepreneurial Capabilities on Marketing Performance Moderated by Market Penetration Strategy (Study on MSMES in Semarang) - Harini, Cicik; Bowo Handayani, Sugeng; Budi Hasiholan, Leonardo; Djohar Djuliani, Retno (Jurnal Multidisiplin Sahombu, 2025)
This study uses digital marketing tools to ascertain how entrepreneurial marketing affects marketing performance in Semarang, Indonesia. The research population The Area Sampling approach and the Stratified Random Sampling Technique were the two steps of the sampling approach used in this investigation. Path analysis using Smart-PLS software was the method of hypothesis testing adopted. The findings demonstrated that entrepreneurial marketing significantly and favorably affects marketing performance and digital marketing skills. Additionally, digital marketing skills positively and significantly impact marketing performance. Nonetheless, there is less chance that digital marketing will mediate the connection between marketing performance and entrepreneurial marketing. Practically speaking, to sustain marketing performance, SMEs must keep enhancing their skills and honing the application of entrepreneurial marketing strategies. Only then can they make the most of their resources to identify opportunities and add value for clients.